2001
DOI: 10.1002/fedr.4921120708
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the genus Fusifilum RAF. 1837 (hyacinthaceae of Southern Africa): 1. Ten new species in the genus fusifilum vel prodromus fusifili revisionis

Abstract: Among the seven species transferred by SPETA (1998: 69–70) to Fusifilum RAF. 1837 there were four true Fusifilum species, and Fusifilum emdeorum sp. nova1 was described by TANG & WEIGLIN (2001). In the present paper ten new species of Fusifilum from South Africa are proposed and, in addition, a fifth old species is transferred from Urginea to Fusifilum resulting in altogether 16 Fusifilum species. The genus Fusifilum was subdivided into the following three sections, viz. F. sect. Archiphysodia, F. sect. Fusifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Regarding the circumscription of this species, Manning & Goldblatt (2007) considered Drimia minor (Duthie 1928: 11) Jessop (1977 as a synonym of Drimia virens (Schlechter 1897: 433) Manning & Goldblatt (2000: 712). However, Urginea minor Duthie (1928: 11) is a distinct species of Fusifilum as shown by the original description "filamenta albida, compressa, 1.5 mm longa, in medio 0.33 mm lata [...] ovarium albidum" (Duthie 1928), a solution in agreement with the latest revision of Fusifilum (Müller-Doblies et al 2001). Furthermore, Duthie (1928) illustrated in her plate number 2 both newly described Urginea pygmaea Duthie (1928: 10) (Plate 2: 1-12) and U. minor (Plate 2: 13-19).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding the circumscription of this species, Manning & Goldblatt (2007) considered Drimia minor (Duthie 1928: 11) Jessop (1977 as a synonym of Drimia virens (Schlechter 1897: 433) Manning & Goldblatt (2000: 712). However, Urginea minor Duthie (1928: 11) is a distinct species of Fusifilum as shown by the original description "filamenta albida, compressa, 1.5 mm longa, in medio 0.33 mm lata [...] ovarium albidum" (Duthie 1928), a solution in agreement with the latest revision of Fusifilum (Müller-Doblies et al 2001). Furthermore, Duthie (1928) illustrated in her plate number 2 both newly described Urginea pygmaea Duthie (1928: 10) (Plate 2: 1-12) and U. minor (Plate 2: 13-19).…”
Section: Introductionsupporting
confidence: 54%
“…Physodia Salisbury (1866: 37) has been considered as a synonym of Fusifilum in recent works. At present, 17 species are accepted in Fusifilum (Müller-Doblies et al 2001, Tang & Weiglin 2001, that form a coherent group easily identified by a distinct morphology such as the stellate flowers with spreading, free tepals, white on the adaxial side with a greenish to purplish longitudinal band on the abaxial side; filaments fusiform and widened in the middle, distinctly papillate on the lower portion; ovary white or tinged with violet or purple, ovate-oblong and commonly truncate to the apex; inflorescence erect at all developing stages; and seeds commonly elliptical in outline, flat and widely winged on the margins (Figs. 1-2).…”
Section: Introductionmentioning
confidence: 99%
“…418) Raf. ex Speta (1998b: 69) is included in the revision of Fusifilum by Müller-Doblies et al (2001). Manning et al (2004) record that these "terminal taxa [were] labelled according to the generic concepts of Speta (1998aSpeta ( , 2001)".…”
Section: Introductionmentioning
confidence: 99%
“…In column D the approach to endemism proposed by MÜLLER-DOBLIES (1996) is further formalized by distinguishing five levels of distribution areas with the digits 1 -5 applied in the present table (as in MÜLLER-DOBLIES et al 2001). Furthermore a preceding symbol indicates the endemism in relation to RSA: asterisk * = taxon endemic to RSA (38 spp.)…”
Section: Distribution Of Androcymbium In Countries and Provinces Ofmentioning
confidence: 99%
“…For the presentation of distribution data, the geographic table for Southern Africa developed by MÜLLER-DOBLIES (1996) (refined by MÜLLER-DOBLIES et al 2001) is used in Tables 5 -7. After the inclusion of two Androcymbium species and one subspecies described by PEDROLA MONTFORT et al (1999a, b), the three distribution tables of Androcymbium in Southern Africa comprise 50 species…”
Section: With 90 Figures (No 39 -128) and 8 Tables Summa Rymentioning
confidence: 99%